What Triage Issues Reveal: Ethics in the COVID-19 Pandemic in Italy and France - Orfali, Kristina (J Bioeth Inq, 2020)
In today’s pandemic, many countries have experienced shortages of medical resources and many healthcare providers have often been faced with dramatic decisions about how to allocate beds, intensive care, or ventilators. Despite recognizing the need for triage, responses are not the same everywhere, and opinions and practices differ around what guidelines should be used, how they should be implemented, and who should ultimately decide. To some extent, triage issues reflect community values, revealing a given society’s moral standards and ideals. Our goal is to study two countries which share many common features—Italy and France—as they deal with the pandemic, revealing the moral organization of medicine and healthcare, the power structures, and the nature of the disruptions in each context.